Lack of T1 hyperintensity in the dentate nucleus after 15 administrations of a macrocyclic contrast agent in multiple sclerosis - Eisele, Philipp; Szabo, Kristina; Alonso, Angelika; Meyer, Melissa; Platten, Michael; Schönberg, Stefan; Gass, Achim (Journal of neurology, neurosurgery, and psychiatry, 2018)
In multiple sclerosis (MS), MRI has emerged as the most useful paraclinical biomarker. ‘No evidence of disease activity’ is a desired outcome in therapeutic clinical trials and therapy monitoring in individual patients, which includes the absence of new or enhancing lesions on MRI. Therefore, frequent follow-up contrast-enhanced MRI examinations play an important role in disease monitoring. In 2013, Kanda et al 1 described an increased signal intensity (SI) of the dentate nucleus (DN) on unenhanced T1-weighted MRI after multiple applications of gadolinium-based contrast agents (GBCAs) suggesting a deposition of gadolinium. Since then, numerous studies evaluated the effects of gadolinium deposition in the brain after serial application of GBCAs, and recent studies provide evidence that T1 hyperintensity of the DN is associated with the prior administrations of linear GBCAs, but not with macrocyclic GBCAs.2 3 However, the experience of an abnormal SI in the DN after more than 15 administrations of GBCAs is limited up to now.2 Since MS typically affects young adults, patients with MS commonly undergo a high number of MRI examinations through their lifetime. The aim of this study was to investigate the effect of 15 or more serial injections of the macrocyclic GBCA gadoterate meglumine on the SI of the DN on unenhanced T1-weighted images in patients with MS. We retrospectively identified patients with relapsing-remitting MS who are at least 18 years of age and who underwent a minimum of 15 gadolinium-enhanced examinations in our institution that were all exclusively performed with the …
Published online first 14 July 2017
Gesehen am 29.11.2018